Running pattern changes after a 38-km trail running race: does shoe fatigue play a role?. (2nd September 2022) - Lloria-Varella, Jaume; Besson, Thibault; Varesco, Giorgio; Espeit, Loïc; Kennouche, Djahid; Delattre, Nicolas; Millet, Guillaume Y.; Morio, Cedric; Rossi, Jeremy
Abstract: The aim of this study was to investigate if acute impairments of the footwear midsole materials could interact with the modifications of the running patterns after a fatiguing trail running race. We hypothesized that introducing a control pair of shoes after the race, would modify running mechanics by partially correcting the alterations generated by the deteriorated properties of the shoes worn during the race. Eighteen participants ran on a treadmill at 10 km·h −1 pre- and post-race in three conditions varying the step frequency (free or fixed) or the footwear (control or personal shoes). Spatiotemporal parameters, tibial accelerations across the running conditions and shoe mechanical properties were measured. Significant changes in shoe characteristics (i.e. reduced thickness and increased stiffness) were measured after the race in the personal footwear. At free step frequency, significant changes in contact (+1.3 ± 3.5%) and flight (−19.4 ± 23.7%) times, step frequency (+2.9 ± 2.9%) and peak-to-peak amplitude acceleration at the tibia level (−3.6 ± 18%) were found. The peak-to-peak amplitude of the mediolateral axis showed a significant shoe × time interaction meaning that the control footwear could have had an impact in the running pattern. However, contrary to our hypothesis, no interaction effects were found between the changes in footwear and the changes in spatiotemporal parameters. In conclusion, impairments of shoes characteristics affect impact but not running mechanics.